ANALISIS KEBUTUHAN HANDOUT DIGITAL PEMBELAJARAN SD BERBASIS TRI N UNTUK MEMBEKALI KETERAMPILAN MENGAJAR MAHASISWA CALON GURU - Anafiah, Siti; Rezkita, Shanta (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2022)
This study aims to analyze the need for digital handouts for teaching elementary school based on Tri N to provide teaching skills for prospective teacher students. This type of research is qualitative research. This study intends to reveal a needs analysis for digital handouts for elementary learning based on Tri N to equip teaching skills for prospective teacher students. The research subjects were undergraduate students of PGSD FKIP UST in semester 4 of the 2020/2021 academic year. The data collection technique in this research used participant observation, interviews, and documentation. Data analysis in this study used interactive model data analysis. The analysis consists of three flows of activities, namely: data reduction, data presentation, and concluding/verification. The results of this study, begin with a needs analysis by identifying the material from the RPS for the Lesson Planning course. In the RPS, materials were found in the form of curriculum analysis, program Prosem, RPP, and attachments (teaching materials, LKPD, learning media, and learning evaluation). In the RPS, the concept of the Tri N teaching has been found, but the teaching materials used are still using printed handouts and PPT. From the analysis of the material, researchers can develop innovative teaching materials, namely digital handouts, so that the material presented can be easily understood and interactive for students.